FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN RUMAH TANGGA TANI DI KOTA BATU (Studi di Desa Tlekung Kecamatan Jonreju Kota Batu) - Johanis Nifanngeljau; Muhamad Rifa’i; Nur Ida Iriani (BUANA SAINS, 2019)
Human resources are very important and must be had in an effort to achieve goals. Human resources are the main element for individuals who compare with other elements, which are supported to develop the existing potential. Capital resources or capital is one means to support the production process of an item or service. Capital does not only consist of technological money, equipment, machinery, land, information, and so on, including capital because it can support the production process. With the capital, the production process will become easier and more efficient, for example, the use of tractors by farmers will increase land management by other manual and traditional methods. Natural resources are resources derived from nature, they can be obtained as valuable goods or services. For example in planting patches in an area will make this area a producer of food or vegetables will be very beneficial for humans if it can be processed properly. In this study, the dominant or significant factor related to human resources has a significant 0,000 0.05 with a standard coefficient of 0.680 or contributes to farm household income of 68.0%. Capital resources have significant ownership of 0.001 0.05 with a standard coefficient of 0.526 or contribute to farm household income by 52.6%. While natural resources have significant ownership of 0,000 0.05 with a standard coefficient of 0.712 or contribute to farm household income of 71.2%. To make this refutation, it is necessary to re-evaluate the group in Tlekung Village, Jonrejo Subdistrict, Batu City, which are human resources, capital resources, and natural resources.